An Evaluation of Participatory GIS (PGIS) for Land Use Planning in Malaysia. Issue 1 (5th December 2017) - Zolkafli, Amirulikhsan; Brown, Greg; Liu, Yan
Abstract: Public participation for land use planning in developing countries is challenged by multiple barriers including low public awareness and engagement with the process. This paper evaluates the capacity of the general public to effectively contribute to land use planning outcomes in Malaysia using Participatory GIS (PGIS). Spatial attributes that identify place values and land use preferences were collected from the public through a web‐based PGIS using facilitated and self‐administered methods and compared with land use zones developed by planning experts. We assessed the quality of the PGIS mapped data by analysing participants' mapping effort and the consistency of the mapped data with existing land use zones. The results indicate logical consistency between the mapped attributes—place values and preferences—and land use zones contained in the expert‐driven land use plans. The results further indicate that the facilitated PGIS process produced higher quality spatial data compared with the self‐administered PGIS survey. Our results suggest that PGIS can provide planning authorities with a viable platform to enhance public participation for land use planning in Malaysia, but that a facilitated PGIS process will be required to increase public participation and the quality of spatial data generated.